Subversive spirituality - Peterson, Eugene H. 1932-; Lyster, Jim; Sharon, John; Santucci, Peter (Grand Rapids, MI Eerdmans, 1997)
Includes bibliographical references.
Keywords: Spiritual life -- Christianity; Spiritual life -- biblical teaching